Age, gender and religiosity as correlates of death anxiety in a rural African context - Mudau, Tshinanne (University of Limpopo (Turfloop Campus), 2012)
This study sought to investigate the relationship of death anxiety to age, gender and religiosity among Africans in a rural South African context. Two hundred participants completed a questionnaire based on demographic variables, death anxiety scales, and a measure of religiosity Results revealed that intrinsic religious motivation was inversely related to all types of death anxiety measured. Furthermore, age was correlated with death anxiety, such that the experience of death anxiety tended to decrease among older subjects. However, there were no gender effects on the experience of death anxiety.
Thesis ( M.A. (Research psychology)) --University of Limpopo, 2012
Keywords: Age; Gender; Religiosity; Death anxiety; 155.93708096; Death -- Psychological aspects.; Death -- Religious aspects.